Kesejahteraan Religius dapat Meningkatkan Spiritual Perawat Covid-19: Religious Welfare Can Improve Spiritual Nurse Covid 19 - Prita Agustiyani; Rindu; Sancka Stella (MPI Press, 2022)
Introduction: Health workers have a higher risk than other industrial workers to experience the risk of contracting covid 19. Nurses as the front line in treating COVID-19 patients have a major role in providing direct services to patients. Objectives: The purpose of this study was to determine the relationship between nurses' religious welfare and nurses' anxiety during the Covid-19 pandemic. Method: This research is a quantitative type with an analytic nature. The research design used is a cross-sectional or cross-sectional study. The population in this study were 35 nurses at the Tapos District Health Center. The sample in this study were 35 people using the sampling technique, namely total sampling. The anxiety research instrument used the Hamilton Anxiety Rating Scale (HARS) instrument and the religious welfare instrument used the Spirituality Well Being Scale (SWBS) instrument. Researchers use the Spearman Test Result: Spearman test results P value = 0.004 means P <0.05. Conclusion: There is a relationship between nurses' religious welfare and nurses' anxiety during the Covid-19 pandemic.